Tert hypermethylated oncologic region (THOR) as a biomarker for breast cancer - Apolónio, Joana (2020)
Breast cancer (BC) is the most frequently diagnosed cancer and a leading cause of death among women worldwide. Early BC is potentially curable, nevertheless, the mortality rates still observed among BC patients, demonstrates the urgent need of novel and more effective diagnostic and therapeutic options. Limitless self-renewal is a hallmark of cancer governed by telomere maintenance. In around 95% of BC cases, this process is achieved by telomerase reactivation through upregulation of human Telomerase Reverse Transcriptase (hTERT). The hypermethylation of a specific region within hTERT promoter, termed TERT Hypermethylated Oncological Region (THOR) has been associated with increased hTERT expression in cancer. However, its biological role and clinical potential in BC has never been studied. Therefore, we aimed to investigate the role of THOR as a biomarker, explore the functional impact of THOR in hTERT upregulation, and also identify other potential DNA methylation-based markers in BC. Firstly, we demonstrated that THOR is significantly hypermethylated in malignant breast tissue when compared to benign tissue (40.23% vs. 12.81%), representing a potential candidate biomarker for future application in BC screening and early diagnosis. Importantly, as DNA methylation marks can be determined from blood samples, assessing THOR methylation status may constitute a non-invasive assay to help in BC management. Next, using a reporter assay, we revealed that THOR acts as a repressive regulatory element of hTERT, and that THOR hypermethylation might be relevant for hTERT upregulation in BC. To further investigate its biological impact on hTERT transcription, targeted THOR demethylation was performed using the CRISPR-dCas9 system. Although, THOR demethylation was achieved, hTERT mRNA levels were not significantly reduced. Surprisingly, cells previously demethylated on THOR region led to a remarkable reduction in tumor development in vivo. Therefore, additional studies are required to validate these observations and to unravel the causality between THOR hypermethylation and hTERT upregulation in BC. Finally, through a genome-wide methylation analysis, we identified three novel DNA methylation markers, located on the PRAC2, TDRD10 and TMEM132C genes that showed diagnostic and prognostic value in BC, as well as in other cancer types. This work evidences the importance of DNA methylation in breast tumorigenesis and, more importantly, their clinical value as promising diagnostic, prognostic and therapeutic targets in BC.